2017
DOI: 10.1039/c7cp03219f
|View full text |Cite
|
Sign up to set email alerts
|

Impact of sequential surface-modification of graphene oxide on ice nucleation

Abstract: Base-washed graphene-oxide which has been sequentially-modified by thiol-epoxy chemistry, results in materials with ice-nucleation activity. The role of hydro-philic/phobic grafts and polymers was evaluated with the most potent functioning at just 0.25 wt %. These 2-D hybrid materials may find use in cryopreservation and fundamental studies on ice formation.The formation and growth of ice crystals presents problems in many fields from aerospace to cell cryopreservation to the automotive industry. Whilst ice fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 21 publications
0
32
0
Order By: Relevance
“…There is also a report of graphene oxide inhibiting ice growth in this concentration range (all growth stopped at 5 mg mL −1 ) . Graphene oxide is also known to affect ice nucleation; such dual activity has also been observed for some AFPs …”
Section: Ice‐binding Self‐assembled Materialsmentioning
confidence: 80%
“…There is also a report of graphene oxide inhibiting ice growth in this concentration range (all growth stopped at 5 mg mL −1 ) . Graphene oxide is also known to affect ice nucleation; such dual activity has also been observed for some AFPs …”
Section: Ice‐binding Self‐assembled Materialsmentioning
confidence: 80%
“…However, others (e.g. Whale et al, 2015;Lupi et al, 2014aLupi et al, , 2014bBiggs et al, 2017) suggested that a lower degree of oxidation leads to enhanced ice nucleation efficiency.…”
mentioning
confidence: 99%
“…Moreover, molecular dynamics calculations show that hydrophilicity is not a sufficient condition for IN (Lupi et al, 2014a, 35 2014b). In fact, Biggs et al (2017) reported an increase in the ice nucleation activity due to a decrease in hydrophilicity.…”
mentioning
confidence: 99%
“…Some studies (e.g., Koehler et al, 2009;Gorbunov et al, 2001;Marcolli, 2014) suggested that heterogeneous ice nucleation is favored on oxidized hydrophilic soot. However, others (e.g., Biggs et al, 2017) suggested that a lower degree of oxidation leads to enhanced ice nucleation efficiency. Our experiments explore the effect of oxidized surfaces.…”
mentioning
confidence: 99%
“…A kinetically based PCF mechanism provides, at least in part, a possible explanation for the widespread IN activity observed for soot particles. This mechanism was formulated to explain ice nucleation by porous materials (Everett, 1961;Blachere and Young, 1972). The PCF mechanism proposes that empty spaces between aggregated primary particles fill with water due to capillary condensation at relative humidities (RH w ) below water saturation, which freezes homogeneously (Higuchi and Fukuta, 1966;Christenson, 2013;Marcolli, 2014;David et al, 2019).…”
mentioning
confidence: 99%